Postural changes in orthodontic patients treated with clear aligners: A rasterstereographic study. (February 2018) - Parrini, Simone; Comba, Benedetta; Rossini, Gabriele; Ravera, Serena; Cugliari, Giovanni; De Giorgi, Ilaria; Deregibus, Andrea; Castroflorio, Tommaso
Abstract: Background: Correlation between malocclusions and body posture has been discussed in the last decades, but there is still a lack of consensus in existing literature. Rasterstereography allows tridimensional reconstruction of the spine, starting from the back surface analysis. So far studies which tested modifications of rasterstereographic parameters during orthodontic treatment, comparing with those obtained from untreated control group, are not available. Clear aligner treatment produces alteration of vertical height due to the occlusal coverage and, subsequently, a stimulation of periodontal receptors which causes an inhibition of the jaw closing muscles and, hypothetically, changes in mandibular posture. Objectives: Evaluate possible correlations between orthodontic treatment and posture. Materials and methods: Rasterstereographic values of 15 untreated patients and of 15 patients treated with clear aligners were compared at baseline, after 1, 3 and 6 months. Rasterstereographic parameters considered were the following: the kyphotic angle, the lordotic angle, the upper thoracic inclination, and the pelvic inclination. Results: Correlations between Kyphosis Angle, Upper Toracic Inclination and Pelvic Inclination and body posture were found after 6 months of treatment with clear aligners. Conclusions: Occlusal coverage caused by aligners could influence body posture not only for upper spine sections but also lower spine sections.